PENGEMBANGAN RUMAH INKLUSI: PENDAMPINGAN UNTUK ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSI - Drajat Tri Kartono; Aris Arif Mundayat; Reza Dian Akbar; Ahmad Zuber; Theofilius Apolinaris Suryadinata (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2022)
This community service is carried out in collaboration with the Yayasan Lembaga Pendidikan Al Firdaus (YLPAF) in Solo City, which organizes inclusive education. YLPAF's inclusive schools include Children with Special Needs (CSN) and regular children in the learning process. ABK requires the presence of a Class Assistant Teacher (CAT) during learning activities, but during the covid-19 pandemic and the application of learning from home, CAT cannot assist directly, so parents carry out the role of the companion. Although face-to-face learning has been re-implemented, the role of a mentor for CSN is still needed when they study at home through an inclusive home approach. Training for regular teachers, class assistant teacher, and parents are carried out to increase knowledge and skills in learning assistance for inclusive homes. The inclusive home approach utilizes learning media in the form of interactive learning videos to help children with special needs learn activities and is added to a companion's presence. The result of the development of the inclusive house is a training module that will be used by the FATAHA Education and Training Center as training materials for YLPAF's own internal and external training participants.